Balancing differential drag with Coulomb repulsion in low earth orbit plasma wakes. (May 2022) - Maxwell, Jordan; Harris, Andrew; Schaub, Hanspeter
Abstract: A novel method for close-proximity formation flying under differential atmospheric drag using Coulomb forces is investigated for applications in Earth sensing, space-situational awareness (SSA), and aeronomy. Objects in LEO are supersonic with respect to the ambient environment, creating a thinned out wake region behind the craft as it travels through the ionosphere. Objects within this wake experience little drag acceleration and are able to attain voltages much greater than in the ambient ionospheric plasma, creating implications for the design and control of close-proximity leader–follower spacecraft pairs. The proposed system consists of a leader craft with a set of affixed, conducting spheres and a charged follower craft located in the wake of the leader. The differential drag acceleration between the leader and follower craft is countered by a controlled Coulomb repulsion to maintain precise separation. The charged structure on the rear of the leader craft is designed such that the charged follower craft sits in an electrostatic potential well which opposes off-axis perturbations. A conceptual method for controlling such a pair without the use of propellant using a set of charged spheres is investigated, with nonlinear models of the system's relative motion derived and discussed. Linearized models are used to demonstrate the local controllability of the system to demonstrate the proposed system's merit. This linear analysis is used to derive conditions on controllability and control performance under different charge geometries and environmental assumptions. Highlights: The use of drag and Coulomb repulsion for control enables precise station keeping. The control sources voltages under 1 kV under perturbations and sensor noise. Centimeter displacements are corrected within a fraction of an orbital period.